The Sexual Risk Context among the FEM-PrEP Study Population in Bondo, Kenya and Pretoria, South Africa - Headley, Jennifer (Public Library of Science, 2014)
BACKGROUND: Incidence rates in the FEM-PrEP and VOICE trials demonstrate that women from diverse sub-Saharan African communities continue to be at substantial HIV risk. OBJECTIVE: To describe and compare the sexual risk context of the study population from two FEM-PrEP trial sites–Bondo, Kenya, and Pretoria, South Africa. METHODS: At baseline we collected information about demographics, sexual behaviors, and partnership beliefs through quantitative questionnaires with all participants (Bondo, n = 720; Pretoria, n = 750). To explore the sexual risk context, we also conducted qualitative, semi-structured interviews with HIV-negative participants randomly selected at several time points (Bondo, n = 111; Pretoria, n = 69). RESULTS: Demographics, sexual behavior, and partnership beliefs varied significantly between the sites. Bondo participants were generally older, had fewer years of schooling, and were more likely to be employed and married compared to Pretoria participants. Bondo participants were more likely to report multiple partners and not knowing whether their partner had HIV than Pretoria participants. A significantly higher percentage of Bondo participants reported engaging in sex without a condom with their primary and other partners compared to Pretoria participants. We found a borderline association between participants who reported not using condoms in the 4 weeks prior to baseline and lower risk of HIV infection, and no association between having more than one sexual partner at baseline and HIV infection. DISCUSSION: Despite significantly different demographics, sexual behaviors, and partnership beliefs, many women in the FEM-PrEP trial were at risk of acquiring HIV as demonstrated by the sites’ high HIV incidence. Though gender dynamics differed between the populations, they appear to play a critical role in women’s sexual practices. The findings highlight different ways women from diverse contexts may be at-risk for HIV and the importance of providing HIV prevention options that are both effective and feasible given personal and social circumstances.